PENGARUH PENERAPAN METODE CARD SORT TERHADAP HASIL BELAJAR AQIDAH AKHLAK DI MADRASAH TSANAWIYAH NEGERI 1 KARANGANYAR - Al Hidayah, Ni'matul Fitryah (STKIP Pesisir Selatan, 2025)
Aqidah Akhlak learning in madrasahs often faces challenges related to monotonous teaching methods and a lack of active student engagement. To address this issue, innovative learning strategies are needed to improve students’ learning outcomes through more interactive approaches. This study aims to determine the effect of implementing the Card Sort method on students’ learning outcomes in Aqidah Akhlak subjects at MTs Negeri 1 Karanganyar in the 2024/2025 academic year. This research uses a quantitative approach with a quasi-experimental design, involving 32 eighth-grade students as research subjects. The instruments used include questionnaires, observation sheets, and achievement tests. Data were analyzed using descriptive and inferential statistics, including Pearson correlation and simple regression tests. The results showed that the implementation of the Card Sort method was at a high category, and students’ learning outcomes significantly improved, with an average score of 90.47. The correlation test showed a very strong relationship between the Card Sort method and learning outcomes (r = 0.893; p < 0.05). The implication of this study highlights the importance of using active learning methods to improve conceptual understanding in Aqidah Akhlak and foster student participation in the learning process.